Penerapan Perangkap Lampu LED Sebagai Upaya Pengendalian Hama Ramah Lingkungan di Lahan Sawah Desa Tawengan - Anditya Gilang Rizky Pradana; Cahyaningtyas Putri Suhita; Desy Setyaningrum; Dewi Nawang Suprihatin; Didik Suryadi; Dimar Hantari; Edi Paryanto; Febry Nurhidayati; Hardian Ningsih; Zainal Arifin (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
Tawengan Village, Sambi District, Boyolali Regency, is an agricultural area where the majority of the population earns their livelihood from rice farming. Rice farmers in Tawengan Village, particularly members of the Amrih Tentrem Farmer Group, face various cultivation challenges, one of the most significant being severe insect pest infestations that reduce rice production. Stem borers, green leafhoppers, rice bugs (Leptocorisa spp.), and other insect pests have caused an estimated 31% decline in rice productivity, as well as deterioration in grain quality. This community service program aimed to address these challenges through the implementation of LED light trap technology as an environmentally friendly pest management method in rice cultivation. The technology utilizes LED light to attract and capture insect pests, thereby suppressing pest populations and reducing pest-related damage without leaving harmful chemical residues. The program was conducted in Tawengan Village, Sambi District, Boyolali Regency. Its implementation consisted of two main activities: educational outreach and apllying the installation of LED light traps. The educational outreach was delivered through interactive presentations, group discussions, and question-and-answer sessions to enhance farmers' understanding of environmentally friendly pest management. Subsequently, the LED light traps were installed using a participatory and demonstrative approach, actively involving farmers in demonstration plots managed by the Amrih Tentrem Farmer Group. This program also contributes to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education) by enhancing farmers' knowledge and technical competencies in implementing environmentally friendly pest management technologies, and SDG 17 (Partnerships for the Goals) by fostering collaboration among universities, the village government, farmer groups, and local farmers in the implementation and dissemination of sustainable pest control technology.